THE INFLUENCE OF AGROCLIMATIC FACTORS ON THE YIELD OF HEMP TRUST BY REGIONS OF UKRAINE - BOІKO, HALYNA; MAKSYMCHENKO, YULIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In the current conditions of post-war reconstruction of Ukraine, the issue of finding new suitable territories for growing agricultural crops, in particular technical hemp, which has high potential as a bioenergy, textile and medicinal crop, is relevant. This problem is particularly relevant in connection with the temporary occupation of certain regions of the country, as well as the contamination of significant areas of agricultural land with explosive objects as a result of hostilities. In this regard, there is an urgent need to study the agroclimatic conditions of different regions of Ukraine in order to determine their suitability for growing crops and obtaining high-quality hemp trust as an alternative to traditional cultivation zones. The purpose of the study is to assess the impact of key agroclimatic factors - average daily temperature, amount and distribution of precipitation, duration of the frost-free period and sums of effective temperatures - on the yield of hemp trust in different climatic zones of Ukraine. The work includes a comparative analysis of indicators from regions traditionally considered suitable for growing industrial hemp (Polissya, Northern Forest-Steppe), and those that could potentially become new centers of production of this crop (Southern Forest-Steppe, part of Central and Western Ukraine).Data from long-term agrometeorological observations were used, as well as the results of field research, which allowed us to identify a close relationship between the level of hemp yield and a set of climatic parameters. Particular attention is paid to the issues of hemp adaptation to new climatic conditions, as well as the risks associated with an increase in the temperature background and uneven precipitation, which are consequences of global climate change.The study found that a number of regions of Central Ukraine have favorable conditions for replacing traditional hemp growing areas and obtaining high-quality hemp, in particular due to a sufficient number of effective temperatures and a stable regime of the growing season. At the same time, emphasis is placed on the need for a comprehensive approach to selecting new locations, which should take into account not only agro-climatic factors, but also socio-economic, logistical, and environmental aspects.
Keywords: hemp trust; agroclimatic conditions; sown areas; comparative analysis; regions of Ukraine; properties